2017
DOI: 10.1371/journal.pone.0178121
|View full text |Cite
|
Sign up to set email alerts
|

Quality of nutrition services in primary health care facilities: Implications for integrating nutrition into the health system in Bangladesh

Abstract: BackgroundIn 2011, the Bangladesh Government introduced the National Nutrition Services (NNS) by leveraging the existing health infrastructure to deliver nutrition services to pregnant woman and children. This study examined the quality of nutrition services provided during antenatal care (ANC) and management of sick children younger than five years.MethodsService delivery quality was assessed across three dimensions; structural readiness, process and outcome. Structural readiness was assessed by observing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(107 citation statements)
references
References 26 publications
8
78
0
21
Order By: Relevance
“…Studies suggest that inaccessibility to public health care facilities, poor availability of medicines and equipment, and perceptions of lower quality diagnosis and treatment drive people away from low cost public facilities. This either increases the use of expensive private sector care where families end up incurring higher out of pocket payment or increase use of untrained informal care providers [ 47 52 ]. Our findings also interestingly suggests that households are faced with worse financial conditions when choosing a private health care provider.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that inaccessibility to public health care facilities, poor availability of medicines and equipment, and perceptions of lower quality diagnosis and treatment drive people away from low cost public facilities. This either increases the use of expensive private sector care where families end up incurring higher out of pocket payment or increase use of untrained informal care providers [ 47 52 ]. Our findings also interestingly suggests that households are faced with worse financial conditions when choosing a private health care provider.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the critical role of IYCF, several major nutrition programmes and policies in Bangladesh that aim to reduce child undernutrition have emphasized IYCF as a key component. These include the National Nutrition Programme (2006–2011), the National Nutrition Services (2011–2016), and the National Strategy on Prevention and Control of Micronutrient Deficiencies (2015–2024; Billah et al, ; Government of the People's Republic of Bangladesh, ; International Food Policy Research Institute, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interviewees reported that concerns about interactions between men and women led to mothersespecially rural mothers and those living in conservative Muslim homes -being uncomfortable in seeking care from male medical practitioners, contributing to delays in seeking care for their children, including post-hospital discharge. A mixed-method study conducted in 12 rural sub-districts of Bangladesh reported that most healthcare providers (60%) managing under-ve year old sick children are male [16]. Another survey conducted in four rural sub-districts noted that many women are only allowed to meet an unknown male health provider to seek care for their children in a dire emergency [40].…”
Section: Discussionmentioning
confidence: 99%
“…Gender related factors at the facility/health system level Fewer female medical practitioners being available in healthcare facilities, particularly in rural areas There was widespread recognition across participants (household members, community representatives and health care providers) that there are fewer female than male medical practitioners available in healthcare facilities, particularly in rural areas; a sex difference documented in national databases [16].…”
Section: Interviewee Characteristics and Overall Treatment-seeking Pamentioning
confidence: 99%